Parsifal: Kertomus Graalin ritarista - Kilpi, Volter, 1874-1939 (Salt Lake City, UT : Project Gutenberg, 2010)
"Parsifal: Kertomus Graalin ritarista" by Volter Kilpi is a novel written in the early 20th century. The story explores themes of purity, sacrifice, and heroism through the lens of the legendary knight Parsifal, who embarks on a quest for the Holy Grail. Central to the narrative is the relationship between Parsifal and his mother, Herzeloyde, alongside the mystical Grail temple and its guardians. The beginning of the novel establishes a richly symbolic setting with the Grail temple, a place of purity and sorrow, where the current king, Anfortas, suffers due to a sin that has tainted his soul and rendered the temple in mourning. As Parsifal grows up under the protective care of his mother, he is both innocent and imbued with a sense of longing for the world beyond their enchanted surroundings. Herzeloyde's deep fears for her son's fate and her memories of a harsh reality instill a sense of foreboding. The opening effectively captures the contrast between the idyllic life of Parsifal and the darker, more complex themes of duty, destiny, and sacrifice that will unfold as he seeks truth in a challenging world. (This is an automatically generated summary.)
Release date is 2010-12-22
Produced by Tapio Riikonen
Keywords: Perceval (Legendary character) -- Romances -- Adaptations